2022-RA-1649-ESGO Mirrors study: a prospective cohort study assessing the feasibility of robotic interval cytoreductive surgery for advanced-stage ovarian cancer. (20th October 2022) - Uwins, Christina; Tailor, Anil; Read, James; Crawshaw, James; Chatterjee, Jayanta; Ellis, Patricia; Skene, Simon; Michael, Agnieszka; Butler-Manuel, Simon
Abstract : Introduction/Background: MIRRORS (Minimally Invasive Robotic surgery, Role in optimal debulking Ovarian cancer, Recovery & Survival) is the largest prospective cohort study of robotic interval CRS in women with advanced-stage epithelial ovarian cancer to date. MIRRORS has investigated the feasibility of consenting, the acceptability and success of robotic interval CRS and its impact on short-term surgical outcomes and quality of life. Aim: to establish the feasibility and safety of a proposed randomised controlled trial (RCT) of robotic interval cytoreductive surgery (CRS) for advanced ovarian, fallopian tube and peritoneal cancer (EOC) using MIRRORS protocol. Methodology: Eligibility: Women with Stage IIIc-IVb EOC undergoing neoadjuvant chemotherapy, suitable for interval CRS with a pelvic mass ≤8 cm. Robot-assisted laparoscopic assessment proceeding to robotic/open interval CRS (MIRRORS protocol). 6-month post-op surveillance. Results: Recruitment: 23/24 eligible women (95.8%). Following MIRRORS-protocol, completed 20 robotic, 3 open interval CRS. All patients achieved CRS to R<1, robotic (tumour site ovary/peritoneum/Tube): R0 =47.4%, open R0 =0.0%. Conversion rate to open: 0.0%. Median estimated blood loss robotic: 50 ml, open: 2026 ml; length of stay 1.5 days robotic vs 6 days open, time to chemotherapy robotic: 18.5 days vs open: 25 days. 6 month OS and PFS are non-inferior compared with concurrent and retrospective control groups. Conclusion: Robotic interval CRS is safe and feasible in women with a pelvic mass up to 8 cm. A prospective RCT is required to assess whether patients undergoing MIRRORS-protocol have non-inferior overall-survival compared to open interval CRS.